(3GdeONd Edi GdedcjI GdacQjI (B:s (3fTCJgG heaghegG hfWGbgG hCgejJgG hJcjagG hJfXjegG hMeGjJgG (B: Introduction to the intellectual property origin concept domain importance adaptation organizing and protection arbitration in Arab countries laws /s - (3Rjf GdOjf, UdGM,s 1957- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3jCJj gPG GdcJGH aj SHYI aUhd JfGhdJ fTCI heaghe hfWGb GdMbhb GdacQjI Ke CgejI GdMbhb GdacQjI, hMeGjI GdMbhb GdacQjI, GdJcjja GdbGfhfj ddMbhb GdacQjI, hGdJfXje ddMbhb GdacQjI, hJMOjK bhGfjf GdMbhb GdacQjI, hGdfghV HGdEHOGY GdYQHj hEf fXGe GdedcjI GdacQjI gOa JYRjR GdJbOe GdGbJUGOj GdGLJeGYj hGdKbGaj ef NdGd MeGjI Mbhb GdedcjI GdacQjI GdJj JDOj Edj JTLjY GdEHOGY aj cGaI GdMbhb aGdGgJeGe HGdMbhb GdacQjI VQhQI hWfjI edMg aj Xd YUQ UfGYj JLGQj RQGYj eJWhQ dPdc GgJe GdeTQY GdCQOfj GgJeGeG eejRG HMbhb GdedcjI GdacQjI dMeGjJgG hbhGfjf NGUI hGgJe HgG GdeTQY GdOhdj cPdc ahVY dMeGjJgG GdGJaGbjGJ hGdeYGgOGJ GdOhdjI(B.s
(3hQO Ydi UaMI GdYfhGf eMce YdejG(B.s
(3edGMb (B: (3UaMI (B225-272.s
(3jTJed Ydi bGFeI eUWdMGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B275-285.s
Keywords: (3Mbhb GdJCdja hGdfTQs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3Mbhb GdJCdja hGdfTQs -- (3GdCQOfs; (3GdESdGe hMbhb GdJCdja hGdfTQs; (3Mbhb GdJCdja hGdfTQ (B((3bGfhf Ohdj(B)s